(2x-1)×0,5-x×0,(3)=(x+3)×0,1(6)
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
x = 2
Explicație pas cu pas:
2x*0.5 - 1*0.5 - x*0.(3) = x*0.1(6) + 3*0.1(6)
1x - 0.5 - x*(3/9) = x*[(16-1)/90] + 3*[(16-1)/90]
x - 5/10 - x*(1/3) = x*(15/90) + 3*(15/90)
x - 1/2 - (1/3)*x = x*(1/6) + 3*(1/6)
x - 1/2 - (1/3)*x = (1/6)*x + 1/2
x - (1/3)*x - (1/6)*x = 1/2 + 1/2
x * [1 - (1/3) - (1/6)] = 2/2
x * [(6 - 2 - 1)/6] = 1
x * (3/6) = 1
x* 1/2 = 1
x = 1/(1/2)
x = 1 * (2/1)
x = 1*2
x = 2
mishodms2005:
multumesc!
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă